Quantifying and Exploring Elementary School Excellence Gaps Across Schools and Time. Issue 4 (November 2019) - Rambo-Hernandez, Karen E.; Peters, Scott J.; Plucker, Jonathan A.
Despite considerable reform activity surrounding K-12 education over the past 20 years, racial and socioeconomic disparities among students who achieve at advanced levels have received little attention. This study examined how excellence gaps, defined as differences in performance at the 90th percentile of subgroups, change over time and their potential antecedents. We analyzed Measure of Academic Progress achievement data in reading and mathematics from a cohort of approximately 60, 000 students from third to fifth grade in 742 elementary schools. Multilevel modeling results indicate that Black/Hispanic and White/Asian excellence gaps were relatively stable in reading. However, excellence gaps in mathematics increased during the school year and across time, and higher achieving schools demonstrated larger excellence gaps than lower achieving schools.